Dopant‐Free Phthalocyanine Hole Conductor with Thermal‐Induced Holistic Passivation for Stable Perovskite Solar Cells with 23% Efficiency. (5th August 2022) - Qu, Geping; Dong, Lei; Qiao, Ying; Khan, Danish; Chen, Qian; Xie, Pengfei; Yu, Xuemeng; Liu, Xiaoyuan; Wang, Yanggang; Chen, Jiangzhao; Chen, Xihan; Xu, Zong‐Xiang
Abstract: Simultaneous passivation of the defects at the surface and grain boundaries of perovskite films is crucial to achieve efficient and stable perovskite solar cells (PSCs). It is highly desirable to accomplish the above passivation through rational engineering of hole transport materials (HTMs) in combination with appropriate procedure optimization. Here, methylthiotriphenylamine‐substituted copper phthalocyanine (SMe‐TPA‐CuPc) is reported as a dopant‐free HTM for PSCs, exhibiting excellent efficiency, and stability. After thermal annealing, SMe‐TPA‐CuPc molecules diffused into the bulk of the perovskite film and effectively passivated the defects in the bulk and at the interface of the perovskite, owing to the strong interaction between the methylthio moiety and undercoordinated lead. The best‐performing annealed SMe‐TPA‐CuPc‐based device shows efficiency of 21.51%, which is higher than the unannealed SMe‐TPA‐CuPc‐based device (power‐conversion efficiency (PCE) of 20.75%) and reference doped spiro‐OMeTAD‐based device (PCE of 20.61%). Further modification of the perovskite of the annealed SMe‐TPA‐CuPc‐based device by the QAPyBF4 additive result in even higher efficiency of 23.0%. It also shows excellent stability, maintaining 96% of its initial efficiency after 3624 h aging at 85 °C. This work highlights the great potential of phthalocyanine‐based dopant‐free HTMs and the defect passivation by thermal‐induced molecular diffusion strategy for developing highly efficient and stable PSCs. Abstract : Methylthiotriphenylamine‐substituted copper phthalocyanine (SMe‐TPA‐CuPc) is synthesized and used as dopant‐free HTM for perovskite solar cells. Owing to the strong interaction between the ‐SMe and undercoordinated lead, SMe‐TPA‐CuPc molecules could diffuse into the perovskite film after thermal annealing and effectively passivate the defects in the bulk and at the interface, which led to high efficiency and thermally stable devices.